Managing fruit cracking in litchi - Kumar, Sunil; Das, Bikash; Dhakad, Ashok; Kumar, Rohit; Kumar, Ganesh (Indian Horticulture, 2026)
Owing to its high economic worth, early maturation, sweet taste, pleasant flavour, and nutritional value, Shahi is a very popular cultivar among Bihar’s litchi growers. Fruit cracking, which occurs at a rate of 10–30% in normal years, has become a major limiting factor in the remunerative cultivation of Shahi litchi. To prevent fruit cracking and reduce financial losses, a comprehensive strategythat holistically considers agronomic and environmental factors is essential. The incidence of cracking can be effectively reduced by bagging litchi bunches (25–30 days after fruit set), foliar spraying of plant growth regulators (salicylic acid at 50 ppm), applying seaweed extract-based bio-stimulants (Sagarika liquid at 0.5%), and ensuring a balanced water supply through an under-canopy micro-sprinkler system.